Identification and characterization of differentially expressed genes in Type 2 Diabetes using in silico approach. (April 2019) - Gupta, Manoj Kumar; Vadde, Ramakrishna
Highlights: T2D related 115 DEGs from GEO dataset & 233 from GWAS catalog were identified. Protein-protein interaction of 348 DEGs identified 99 key hub genes. Five genes ( CCL2, ELMO1, VEGFA, FOS, & TCF7L2) playing major role in T2D. Target miRNA, TFs and potential drugs identified for T2D hub genes. Abstract: Diabetes mellitus is clinically characterized by hyperglycemia. Though many studies have been done to understand the mechanism of Type 2 Diabetes (T2D), however, the complete network of diabetes and its associated disorders through polygenic involvement is still under debate. The present study designed to re-analyze publicly available T2D related microarray raw datasets present in GEO database and T2D genes information present in GWAS catalog for screening out differentially expressed genes (DEGs) and identify key hub genes associated with T2D. T2D related microarray data downloaded from Gene Expression Omnibus (GEO) database and re-analysis performed with in house R packages scripts for background correction, normalization and identification of DEGs in T2D. Also retrieved T2D related DEGs information from GWAS catalog. Both DEGs lists were grouped after removal of overlapping genes. These screened DEGs were utilized further for identification and characterization of key hub genes in T2D and its associated diseases using STRING, WebGestalt and Panther databases. Computational analysis reveal that out of 99 identified key hub gene candidates from 348 DEGs, only four genes ( CCL2, ELMO1, VEGFA and TCF7L2 ) along with FOS playing key role in causing T2D and its associated disorders, like nephropathy, neuropathy, rheumatoid arthritis and cancer via p53 or Wnt signaling pathways. MIR-29, and MAZ_Q6 are identified potential target microRNA and TF along with probable drugs alprostadil, collagenase and dinoprostone for the key hub gene candidates. The results suggest that identified key DEGs may play promising roles in prevention of diabetes.